Reliability and Rationing Cost: Some Analytical Implications for a Power System - Pillai N, Vijayamohanan (Asian Journal of Energy Transformation and Conservation, 2015)
The present paper attempts to analyze the implications of the relationship between reliability and rationing cost involved in a power supply system in the framework of the standard inventory analysis, instead of the conventional marginalist approach of welfare economics. The study is substantiated by fitting a normal distribution to the daily internal maximum demand of the Kerala power system during the four-year period from 2010-11 to 2013-14, and also by estimating, based on the techno-economic parameters of a 660 MW thermal power plant, the rationing costs implied in different reliability target criteria.